Stability and postcritical behavior of two-layer cylindrical shells with non-adherence area subjected to axial compression - Obodan, N. I.; Prokopalo, E. F.; Gromov, V.A. (Reports of the National Academy of Sciences of Ukraine, 2014)
Critical loads and postbuckling behavior for an axially compressed two-layered cylindrical shell with non-adherence area are considered. It is revealed that the loss of stability proceeds in two phases: a localized deformed shape emerges in the non-adherence area site following by the general loss of stability (loss of load-carrying capability).